2019
DOI: 10.1111/cei.13294
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of naive, activated and memory T and B cells in blood of patients with ulcerative colitis or Crohn’s disease

Abstract: Summary Both major subcategories of inflammatory bowel disease (IBD), ulcerative colitis and Crohn’s disease are characterized by infiltration of the gut wall by inflammatory effector cells and elevated biomarkers of inflammation in blood and feces. We investigated the phenotypes of circulating lymphocytes in the two types of IBD in treatment‐naive pediatric patients by analysis of blood samples by flow cytometry. Multivariate analysis was used to compare the phenotypes of the blood lymphocytes of children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…Furthermore, to clarify the functional roles of immune cells on the UC pathogenesis, we estimated the immune cell proportions in all the samples. The accumulated effector CD8 and reduced proportion of naïve CD4 might be responsible for the adaptive immune response in UC, showing consistency with the previous study [ 33 ]. Notably, BACH2 and EGR2 could regulate CD8 cell differentiation, indicating that the high proportion of CD8 + might be associated with the upregulation of BACH2 and EGR2 [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, to clarify the functional roles of immune cells on the UC pathogenesis, we estimated the immune cell proportions in all the samples. The accumulated effector CD8 and reduced proportion of naïve CD4 might be responsible for the adaptive immune response in UC, showing consistency with the previous study [ 33 ]. Notably, BACH2 and EGR2 could regulate CD8 cell differentiation, indicating that the high proportion of CD8 + might be associated with the upregulation of BACH2 and EGR2 [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, AQP9 was showed to play a role in regulating tissuespecific physiological properties in tight junctions in ulcerative colitis (25). Regarding the CD27 in CD, reduced CD27 -IgD -B cells in the blood and raised CD27 -IgD -B cells was found in the gut-associated lymphoid tissue in IBD (26), study also observed that patients with CD were characterized by a reduced proportion of B cells of the memory CD27+ phenotype compared to the non-IBD controls (27). In term of HVCN1, expression of HVCN1 was found to significantly positively correlate with the clinical activity of CD (28).…”
Section: Discussionmentioning
confidence: 78%
“…Enrichment analyses of the genes in the key modules of the constructed PPI network revealed that they were mainly enriched in some immune-related pathways and cellular organization processing, such as leukocyte cell-cell adhesion, extracellular matrix organization, T cell activation, and leukocyte migration. The adhesion and migration of leukocyte, as well as the activation of T cells have been linked to the pathogenesis of UC and RA ( Thomas and Baumgart, 2012 ; Reynisdottir et al, 2016 ; McNaughton et al, 2018 ; Rabe et al, 2019 ). Finally, a total of 45 hub genes were identified, among which four hub genes ( SRGN, PLEK , and FCGR3B ) were predicted to be upregulated in UC and RA samples (GSE38713 and GSE1919) and downregulated in UC patients with response to infliximab treatment (GSE12251).…”
Section: Discussionmentioning
confidence: 99%